Drivers of preventable high health care utilization: a qualitative study of patient, physician and health system leader perspectives. Issue 4 (October 2020) - Das, Lala Tanmoy; Kaushal, Rainu; Garrison, Kelsey; Carrillo, Vanessa; Grinspan, Zachary; Theis, Ryan; Shenkman, Elizabeth; Abramson, Erika
Objectives: A small percentage of patients account for the bulk of population health care utilization and costs in many countries including the United States (US). In the US, 5% of the population has high health care utilization accounting for nearly 50% of health care costs. A subset of this utilization is deemed preventable, and thus potentially cost saving to patients as well as to the health care system. This study sought to identify drivers of preventable utilization from the perspectives of three stakeholder groups in the US: health system leaders; high-need, high-cost (HNHC) patients or their primary caregivers; and physicians. Methods: We performed a qualitative study using interviews of health system leaders and focus groups of HNHC patients, caregivers and physicians. We used a mixed inductive deductive approach to analyse transcripts and identify themes. Results: We identified three key drivers of preventable high health care utilization: (1) unmet behavioural health needs, (2) socio-economic determinants of health and (3) challenges associated with accessing health care delivery systems. Conclusions: To be potentially more effective, interventions to reduce preventable high health care utilization should incorporate the perspectives of patients, health system leaders and physicians. Particularly important to stakeholders is increased access to mental-health resources, support for patients with low socio-economic resources and systemic changes that reduce wait times for primary care visits and allow providers more time during patient visits.